2016
DOI: 10.1152/jn.00326.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scratching and other counterstimuli on responses of trigeminothalamic tract neurons to itch-inducing stimuli in rats

Abstract: Lipshetz B, Giesler GJ Jr. Effects of scratching and other counterstimuli on responses of trigeminothalamic tract neurons to itchinducing stimuli in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
(58 reference statements)
1
7
1
Order By: Relevance
“…Yosipovitch et al (2007) applied alternating thermal stimuli 3 cm distally to a site of histamineinduced itch (i.e., intra-segmentally) and still observed significant antipruritic effects for stimuli intensity in, or close to, the noxious range (Yosipovitch et al 2007). Interestingly, a recent study documented that pruriceptive signaling is only significantly reduced by homotopic scratching and hence other counter-stimulation modalities appear to rely on different mechanisms of itch inhibition (Lipshetz and Giesler 2016). Seemingly contradictory to our results, Murray and Weaver (1975) found a decrease of itch intensity in response to a contralaterally applied modified cold pressor pain stimulus.…”
Section: The Perception Of Itch Is Not Modulated By Conditioning Paincontrasting
confidence: 99%
See 1 more Smart Citation
“…Yosipovitch et al (2007) applied alternating thermal stimuli 3 cm distally to a site of histamineinduced itch (i.e., intra-segmentally) and still observed significant antipruritic effects for stimuli intensity in, or close to, the noxious range (Yosipovitch et al 2007). Interestingly, a recent study documented that pruriceptive signaling is only significantly reduced by homotopic scratching and hence other counter-stimulation modalities appear to rely on different mechanisms of itch inhibition (Lipshetz and Giesler 2016). Seemingly contradictory to our results, Murray and Weaver (1975) found a decrease of itch intensity in response to a contralaterally applied modified cold pressor pain stimulus.…”
Section: The Perception Of Itch Is Not Modulated By Conditioning Paincontrasting
confidence: 99%
“…This is in accordance with an earlier study using a similar study design, in which CPM effect was found for pressure pain thresholds and suprathreshold heat stimulation but not for mechanical detection thresholds or warmth detection thresholds (Leffler et al 2002). Interestingly, the inhibition of itch by application of various homotopic or intra-segmentally applied counter-stimuli is well established, while itch inhibition by application of counter-stimuli far away from the area of induced itch is much less studied (Bromma et al 1995;Yosipovitch et al 2005;Pfab et al 2006;Lipshetz and Giesler 2016;van Laarhoven et al 2016). Noxious thermal or mechanical stimuli such as pinching or scratching in or close to an area of induced itch will greatly diminish the magnitude of the experienced itch transiently.…”
Section: The Perception Of Itch Is Not Modulated By Conditioning Painsupporting
confidence: 90%
“…Most RVM ON cells were excited by pruritogens and scratching the skin, and OFF cells were inhibited by both. Scratching inhibited the pruritogen-evoked responses of spinal neurons (Akiyama et al 2011(Akiyama et al , 2012bDavidson et al 2009;Lipshetz and Giesler 2016;Nishida et al 2013). Scratch inhibition of spinal pruriceptive neurons was partially reduced by spinal transection, implying the involvement of both segmental and supraspinal inhibitory mechanisms (Akiyama et al 2011).…”
Section: Scratching and Descending Pathwaysmentioning
confidence: 99%
“…Interestingly, in a recent preclinical study, central neuronal firing levels evoked by intradermal pruritogen injection (serotonin) were not reduced by transient noxious heat stimuli (45°C and 50°C for 5 s). 58 However, another study showed that neuronal activation (following dry skin induction) in the superficial dorsal horn was reduced by a longer noxious heat stimulus (48-56°C for 20 s). 59 These findings could suggest that with transient counterstimuli, the upper level of itch transduction remains unchanged, but the inhibitory effect observed in this study relied on peripheral mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a recent preclinical study, central neuronal firing levels evoked by intradermal pruritogen injection (serotonin) were not reduced by transient noxious heat stimuli (45 °C and 50 °C for 5 s) . However, another study showed that neuronal activation (following dry skin induction) in the superficial dorsal horn was reduced by a longer noxious heat stimulus (48–56 °C for 20 s) .…”
Section: Discussionmentioning
confidence: 99%